Disaster preparedness awareness among critical care nurses at a tertiary hospital in Pahang, Malaysia - Azali, Nurul Aqila; Mohamed Ludin, Salizar (Lincoln University College, Malaysia, 2020)
Background:Disaster preparedness should be taken seriously as preventive measures and it is one of the elements in the disaster risk reduction framework but the status the country is unknown. Methods and materials: A cross-sectional study was done using Disaster Preparedness Evaluation Tool to investigate the relationship between factors contributing to disaster preparednessof on 125 critical care nurses toward their preparedness in a disaster. Findings:Thefacility where the nurses workshowed significant contributionto disaster preparedness (p <0.05). Variables that shows strong relationship and positively correlated are knowledge (r = 0.654, p = 0.001), skills (r = 0.727, p = 0.001) and perception: r = 0.737, p = 0.001). Discussion: The finding is similar to (Tzeng et al., 2016) that found disaster preparedness to have a significant association with participants’ educational level, emergency or intensive care experience, number of years in nursing and their background. Disaster experience was found to be influencing the willingness to respond (Goodhue, et al., 2012; Baack and Alfred, 2013). (Sonneborn, Miller, Head, and Cross 2018) also emphasized the nurses' required disaster training annually.Conclusion:Overall, there was a significant association between the level of knowledge, skills and perception toward disaster preparedness with the level of disaster preparedness. Training is needed to create awareness and preparedness.